A promising CO2 methanation catalyst system based on modified halloysites as supports - Ahmed Gamal (14112864) (2025)
Earth’s climate is warming due to anthropogenic emissions of greenhouse gases, especially carbon dioxide (CO2). Different reactions are allocated to mitigate the CO2 in the atmosphere. However, CO2 methanation is a pivotal research hotspot due to its ability to produce methane at low operating temperatures (200–400 °C). Halloysite nanotubes (HNTs)-based catalysts have attracted significant attention in various catalytic applications. However, Halloysite is rarely reported for thermal CO2 methanation. The selected halloysite clay was modified first using the 3-Aminopropyl triethoxy silane (NH2) as coupling agent, the resulting materials (HNTs), and then doped with Ni at different weight concentrations (5%, 10%, 20%, 40%, 50%). materials can offer high surface area and porous structure, which can improve metal dispersion. The prepared Ni/HNTs catalysts were characterized using various techniques, such as XRD, XPS, SEM, and TEM, which confirmed the existence of nanotubes and porous structures. The propensity of the prepared Ni/HNTs were evaluated to catalyse the CO2 methanation reactions at a temperature range of 250 to 500 ̊C. The catalyst containing 20 wt.% of Ni (20Ni/HNTs) showed the highest CO2 conversion at all reaction temperatures and the highest selectivity of methane at 450 °C (82%). This study paves the way for the large utilization of the HNTs as a strong support for different metals used in thermal catalytic reactions, not limited to the CO2 methanation. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-024-00929-1